The Role Of Influencer Credibility And Content Authenticity On Consumer Purchase Intention For Skintific Product - Nudya Layalia; Siska Ernawati Fatimah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
In the digital era, social media has become a key platform influencing consumer purchase decisions, particularly through influencer marketing. However, the effectiveness of influencer credibility and content authenticity in shaping purchase intention remains a critical issue. This study aims to evaluate the role of influencer credibility and content authenticity on consumer purchase intention for Skintific products in the Cirebon area. The research employs a quantitative approach using Structural Equation Modeling (SEM). Data were collected through an online survey using a Likert scale, involving 240 respondents selected through purposive sampling. The findings indicate that both influencer credibility and content authenticity significantly influence purchase intention, with content authenticity showing a stronger effect. Additionally, the interaction between these variables significantly contributes to shaping consumer purchase behavior. This study provides insights into digital marketing strategies by emphasizing the importance of influencer trustworthiness and authentic content in influencing consumer decisions.